STATE ANXIETY INVENTORY SCORE AMONG STUDENTS WITH FINAL ASSIGNMENT - Imandiri, Ario; Widyastuti, Erlinda; Jonosewojo, Arijanto (Journal of Vocational Health Studies, 2017)
Background: Students final assignment is a scientific work requires precision, time consuming, energy as well as concentrations. Students may experience stress within the process of completing the final assignment, which can lead to variety of disorder; physical, emotional, intellectual and interpersonal. Purpose: The aim of this study was to determine the state anxiety inventory scores among final students with scientific project. Those score were then being used as preliminary data to decide the next step of the study which are giving acupuncture therapies to those students with high score of anxiety.  Method: This was a descriptive study with one shot/cross sectional study, using questionnaires distributed to respondents for data completion. Respondents were 100 students from Faculty of Vocational Education Universitas Airlangga who were taking the final assignment subject. Result: The results of State Anxiety Inventory Score were obtained as average score of 53.03 with standard deviation of 10.4. Conclusion: The mean values showed a reasonably anxious outcome.